Prakondisi Desa Digital di Desa Tamboo Kecamatan Bone Pantai Kabupaten Bone Bolango - Yusuf, Taufiq Ismail; Salim, Sardi; Irawaty, Ade; Dako, Amiruddin; Dako, Rahmat; Dali, Sri Wahyuni; Hidayat, Ikhsan (Universitas Negeri Gorontalo, 2019)
Rural development has undergone significant changes since the digitization of Information and Communication Technology (ICT). Hybrid media technology has proven to make it easier for innovative villages to build networks and empower their communities to narrow the ICT gap, one of which is through community service. This community service is an effort of Gorontalo State University so that the Tridarma of Higher Education is implemented to contribute science and technology to the community. This Community Service was carried out in Tamboo Village, Bone Pantai District, Bone Bolango Regency. The purpose of this Community Service was to provide counseling on how to condition the beginning of a village so that it becomes a digital village. The expected output targets from this activity are: 1) The officials and community in Tamboo Village have knowledge of the importance of the village internet and how to manage infrastructure related to the village internet. 2) Village officials or village internet managers can have the ability to use internet facilities, which can then be developed to create village websites for digitization: village profile data, population data, village resource and potential data and other activities that can be digitized for work effectiveness and efficiency.